Cloud Enterprise Resource Planning - แซ่จึง เจริญศักดิ์ (Business Administration and Management Journal Review, 2019)
This article presents an overview of cloud enterprise resource planning with an attempt to create an understanding of the systems to organization’s executives and information systems decision makers. The first section of the article covers an overview and scope of enterprise resource planning (ERP) as well as its advantages and disadvantages in order to point out the strengths and weaknesses of an on-premise ERP. The second part includes cloud computing concepts, cloud computing delivery models, cloud computing deployment models and ERP deployment models. This part intends to relate the cloud computing technology to ERP. The third part presents benefits and challenges of a cloud ERP comparing to an on-premise ERP. The last section of the article includes some additional issues regarding migration from on-premise to cloud ERP and blockchain in cloud ERP in order to illustrate the transition to cloud ERP as well as putting an emerging technology onto cloud ERP respectively.